2018
DOI: 10.1089/env.2018.0003
|View full text |Cite
|
Sign up to set email alerts
|

Hurricanes and the Environmental Justice Island: Irma and Maria in Puerto Rico

Abstract: This article presents an overview of our research team’s disaster response to the massive destruction of Hurricanes, Irma and Maria, in September 2017, in light of the 120-year colonial legacy and long-term, widespread environmental contamination in Puerto Rico. Both local and federal governmental responses have been extremely inadequate, especially in light of the long-standing issues of environmental contamination throughout the island. Community organizations in Puerto Rico have been fighting for environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…1,2 HM directly killed 64 people in PR with excess deaths estimated from 990 1 to 4645, 3 destroyed over 90% of the electrical systems and 80% of the agricultural sectors, and left large areas without communication, water, and health care services, all of which resulted in an extremely slow posthurricane recovery. 1,4 Limited studies on the impact of HM have reported increasing rates of adverse physical and psychological health consequences (e.g., fall-related injuries, leptospirosis infection, anxiety, post-traumatic stress) 5−8 and hurricane-exacerbated environmental effects including persistent hydrological disruption, 2 deterioration of coastal water quality, 9 increased air pollution, 4 and disturbance of forest ecosystems. 10,11 However, little is known about the disruption of HM on drinking water quality that is critical to waterborne/ water-related disease control and public health protection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1,2 HM directly killed 64 people in PR with excess deaths estimated from 990 1 to 4645, 3 destroyed over 90% of the electrical systems and 80% of the agricultural sectors, and left large areas without communication, water, and health care services, all of which resulted in an extremely slow posthurricane recovery. 1,4 Limited studies on the impact of HM have reported increasing rates of adverse physical and psychological health consequences (e.g., fall-related injuries, leptospirosis infection, anxiety, post-traumatic stress) 5−8 and hurricane-exacerbated environmental effects including persistent hydrological disruption, 2 deterioration of coastal water quality, 9 increased air pollution, 4 and disturbance of forest ecosystems. 10,11 However, little is known about the disruption of HM on drinking water quality that is critical to waterborne/ water-related disease control and public health protection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…are several orders of magnitude lower that what has been published in literature (Huang et al, 2021;Isaac and Sherchan, 2020;Ley et al, 2020;Liu et al, 2019) (i.e., 1-10 4 copies mL -1 ). A potential reason for this could be over-chlorination in the systems, which had been reported in the aftermath of HM (Brown et al, 2018), including in early phase of sampling as this study showed.…”
Section: Microbial Communities and Metagenomes Of Pr Samples Were Similar To Those Seen Inmentioning
confidence: 70%
“…Another chemical exposure that continues to pose a problem in post-Maria Puerto Rico is heavy-metal-laden coal ash contamination. 8 These types of chemical exposures will lead to short-and long-term health outcomes in any disaster setting, such as chronic heavy metal poisoning and, possibly over time, cancer. Specifically, in terms of children's postdisaster health, there are no mandated federal, state, or local inspections of damaged educational facilities for the safe re-occupancy by children.…”
Section: Natural Disaster As a Critical Period: Hurricane Maria On Pumentioning
confidence: 99%